An Overview of Methods Used in the Determination of Soil Hydraulic Conductivity - Musa, J.J.; Gupa, Y.U. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2019)
Hydraulic conductivity is one of the most important parameter for flow and transport related phenomena in soil.There is concern arising from the suitability, efficiency and ease of the different measuring methods under differentconditions. The various methods of determining hydraulic conductivity include field, laboratory and correlationmethods each with individual merits and demerits. Although selection of a specific method for a particularapplication will depend on the objectives to be achieved, most researchers prefer direct measurement of soilhydraulic conductivity. The estimation of soil hydraulic conductivity using correlation method depends on the localsoil maps, soil particle size distribution, organic matter content and bulk density. Field methods are usually moreexpensive than laboratory methods. Consequently, when the question of cost becomes decisive, or when actualrepresentation of field conditions is not of fundamental importance and in-situ hydraulic conductivity is notavailable, laboratory methods may be used to determine the saturated hydraulic conductivity K. Overall, this reviewexplains the various methods that can be used to determine hydraulic conductivity in-situ or within the laboratory.